Strategi Kepemimpinan Kepala Desa Dalam Menggerakkan Partisipasi Warga Untuk Mewujudkan Desa Wisata Perean Kangin Kecamatan Baturiti, Kabupaten Tabanan - Anak Agung Ketut Sri Candrawati; I Ketut Sukantha Artha Wibawa; I Nyoman Janayasa (Universitas Warmadewa, 2026)
This study analyzes the leadership strategies employed by the Village Head of Perean Kangin to mobilize community participation in realizing a Tourism Village. Using a qualitative case study approach, the research found that a transformational-participatory leadership style—characterized by collective vision building, dialogical communication, institutional empowerment, role modeling, and non-material recognition—successfully fostered a sense of ownership, mobilized local resources, and shifted villagers from objects to subjects of development. The findings highlight that effective mobilization of participation depends on trust, empowerment, and the internalization of a shared vision.